Singapore: from an unfeasible country, to a world model (2014)
Singapore, considered an unfeasible country before 1960, became a world model today. Registering some of the best indexes globally, in several aspects: it is one of the largest financial and commerce centers in the world; it is the second most important port, with greater volume of activity; its water resource management policies and infrastructures are some of the most efficient; It is classified as the third country with the highest income per capita at a global level, in addition to being among the first countries in the international lists of education, health, political transparency and economic competitiveness.